"Charmingly delicious": childhood obesity and General Mills' dilemma. Issue 2 (1st August 2014) - Yordy, Eric D.; Paden, Nita; Bryant, Katlin
Abstract : Synopsis: In 2010, approximately one-third of US children and adolescents were classified as at least overweight, with 17 percent classified as obese. In addition to other causes, the marketing and advertising of food directly to children was identified by a Task Force on Childhood Obesity as a contributing factor. As a result, food industries began to self-regulate. Consumer advocacy organizations developed guidelines for advertising products targeted to children. Cereal companies, such as General Mills (GM), struggled with whether or not to adopt those standards. GM began to change both marketing and product advertising in small ways. The changes were considered steps in the right direction but GM continued to be under scrutiny of advocacy groups. This case addresses the struggle of General Mills to make changes to product nutritional content and/or marketing and to address the societal concern about childhood obesity while also meeting responsibilities to consumers and shareholders. Research methodology: The case was researched utilizing secondary data – all materials are readily available to the public. There is no disguise of any actual person or entity and no relationship between the authors and the organizations or individuals mentioned in the case. Frequent sources include the General Foods, Children's Food and Beverage Advertising Initiative and Center for Science in the Public Interest web pages. Relevant courses and levels: This case could be used at an undergraduate or graduate level. Legal Environment of Business, Business Ethics and any Marketing course. Theoretical basis: The ethics frameworks in most business law or ethics textbooks may be used to discuss the dilemma identified in this case. This Instructor's Manual uses Hosmer's model. Hosmer (2008), The Ethics of Management: A Multidisciplinary Approach, 7th ed.